ANALISIS KESALAHAN MENYUSUN KALIMAT BAHASA JERMAN - Herlin Herlin; Laelah Azizah; Syarifah Fathimah (Makassar State University, 2018)
The purpose of this study was to obtain data and information about errors and percentage of students' errors in composing German sentences. The research design used in this study is descriptive method. To analyze the data used the percentage technical formula and in the data collection used a written test to determine students' errors in German language sentences, German question sentences and German command sentences. The results of this study indicate that, errors in composing German language news sentences 33.03%, errors in composing German question sentences 42.55% and errors in composing German command sentences 49.52%.